Shell-based genus-level reclassification of the Family Vasidae (Mollusca: Neogastropoda) - Vermeij, Geerat J. (Zootaxa, 2024)
The neogastropod family Vasidae comprises a small group of Late Eocene to Recent neogastropods with large, often ornate shells. A new, shell-based morphological classification of the family is proposed, in which ten genera are recognized: Altivasum Hedley, 1914, Aristovasum gen. nov. (type species: Turbinella cassiforme Kiener, 1840), Florivasum gen. nov. (type species: Turbinella tubifera Anton, 1838), Globivasum Abbott, 1950 (type species: Turbinella nuttingi Henderson, 1919, but expanded here), Hystrivasum Olsson & Petit, 1964 (type species: Vasum horridum Heilprin, 1887), Rhinovasum gen. nov. (type species: Voluta rhinoceros Gmelin, 1791), Siphovasum Rehder & Abbott, 1951, Tudivasum Rosenberg & Petit, 1987, Vasum Röding, 1798 (here restricted to a reef-associated group of three species typified by Murex turbinellus Linnaeus, 1758), and Volutella Perry, 1810 (here resurrected from synonymy with Vasum, type species Voluta muricata Born, 1778). Biogeographically the Vasidae exhibit a deep divergence between the Atlantic-East Pacific and Indo-West Pacific realms dating to the Early Miocene.